Signal transducer and activator of transcription 3 as a potential therapeutic target for Graves’ orbitopathy - Ko, JaeSang; Kim, Ji-Young; Kim, Bo Ram; Lee, Eun Jig; Kikkawa, Don O.; Yoon, Jin Sook (Molecular and cellular endocrinology, 2021)
The roles of signal transducer and activator of transcription 3 (STAT3) in inflammation, oxidative stress, and adipogenesis during Graves’ orbitopathy (GO) are incompletely understood. Here, STAT3 expression in orbital tissues (from individuals with GO and healthy control subjects) was studied, and the role of STAT3 in GO pathogenesis was examined through small-interfering RNA (siRNA)-mediated silencing in primary orbital fibroblasts. STAT3 mRNA expression was higher in GO orbital tissues than in non-GO tissues. Treatment with proinflammatory cytokines, thyroid-stimulating hormone, or insulin-like growth factor-1 induced STAT3 mRNA in GO orbital fibroblasts, but not in non-GO cells. STAT3 silencing inhibited interleukin-1β-induced inflammatory cytokines and oxidative stress-induced haem oxygenase-1 expression. STAT3 siRNA-transfected GO orbital fibroblasts showed decreased adipocyte differentiation. STAT3 affected proinflammatory cytokine production, oxidative stress responses, and adipogenesis in an in vitro model of GO, suggesting that STAT3 mediates GO pathology, and that modulating STAT3 expression may have therapeutic potential against GO. •STAT3 mRNA was significantly elevated in GO orbital tissues vs. control tissues.•Stimulant treatments specifically induced STAT3 mRNA in GO orbital fibroblasts.•STAT3 silencing inhibited induced inflammatory cytokine and HO-1 expression.•STAT3 silencing decreased adipocyte differentiation and transcription factors.•STAT3 affected proinflammatory cytokines, stress responses, and adipogenesis in GO.